Community resilience through the lens of social support: Recovering from the 2010 Eyjafjallajökull eruption in Iceland. (15th October 2022) - Ómarsdóttir, Ingibjörg L.; Pétursdóttir, Guðrún; Bird, Deanne K.; Gísladóttir, Guðrún
Abstract: This qualitative study investigated the role of different forms of social capital – bonding, bridging, and linking – in the recovery of families affected by the 2010 Eyjafjallajökull eruption in Iceland. We interviewed 44 residents in three generations of 12 families, living in the vicinity of the volcano: five in a village and seven in a farming community. We explored what types of social support were considered essential for the recovery, and how these may best be offered for the benefit of the affected community. The results revealed that the families had strong bonding and bridging networks that provided essential support from the onset of the eruption. The linking social capital provided all types of social support which was considered a vital coping and recovery factor. However, our results reveal various aspects of the services which can be improved. Equity in access to social support is essential. While bonding and bridging social capital depend on the connections families may have, linking social capital must not rely on personal ties. It needs to be organised by formal agents, be accessible to all affected, and provided for as long as needed. The study contributes to the understanding of the importance of social support when dealing with the impacts of adverse natural events. It highlights the need for strong linking social capital when aiming for community resilience. Efficient social support measures call for close cooperation and coordination between various agents whose daily tasks may not include disaster management. Graphical abstract: Image 1